Asset Management Efficiency and Teachers’ Satisfaction with Educational Facilities in a Selected School in Yunnan, China - Han, Fei (Pacific International Journal, 2025)
This study investigates the relationship between asset management efficiency and teachers’ satisfaction with educational facilities at Kunming University of Media and Communication in Yunnan, China. Utilizing a descriptive-comparative-correlational design, data were collected from 242 teachers through a structured questionnaire assessing their perceptions of resource availability, maintenance, allocation, and their resultant satisfaction with facilities. Findings indicate that teachers generally perceive asset management as effective and report satisfactory facility conditions. A significant positive correlation was identified between sustainability practices and teacher satisfaction. While demographic factors like age and gender showed no significant impact on these perceptions, the study concludes that efficient, sustainable asset management is integral to fostering a supportive educational environment. The results provide a basis for developing targeted programs to enhance resource allocation and maintenance protocols, thereby improving overall teacher satisfaction and educational outcomes.